Debates Over Liberalising Dual Citizenship: Prospects And Limits In Taiwan And The People's Republic Of China - Low , Choo (Penerbit Universiti Sains Malaysia (USM Press), 2015)
This article examines the politics of dual citizenship in Taiwan and the People's Republic of China (PRC). While the immigrants in Taiwan are proposing to expand the privileged right of dual citizenship to non-Republic of China (ROC) nationals, the Chinese emigrants are demanding the right to retain their Chinese citizenship on their acquisition of foreign citizenship. Despite the continuous lobbying, both governments are reluctant to liberalise their existing citizenship law. The liberal preposition which situates dual citizenship in a human rights framework is unacceptable to both states. This article suggests that the political cultures of Taiwan and China are incompatible with the liberalist approach of citizenship